Spontaneously Arising Tumours and Tumour-like Lesions of the Cervix and Uterus in 83 Pet Guinea Pigs (Cavia porcellus). Issue 4 (May 2017) - Laik-Schandelmaier, C.; Klopfleisch, R.; Schöniger, S.; Weiffenbach, G.; Staudacher, M.; Aupperle, H.
Summary: Tumours and tumour-like lesions are rare findings in the genital system of guinea pigs. The aim of the present study was to characterize nodular lesions in the cervix and uterus of guinea pigs submitted for histopathological diagnosis. Samples from 83 pet animals were investigated. Cases included 64 surgically excised masses including complete uteri ( n  = 37), parts from uteri containing masses ( n  = 8), complete masses ( n  = 12) or samples from masses ( n  = 7) and 19 complete necropsy examinations. In 55 of the cases, only solitary changes were observed; in 28 cases two or more lesions were diagnosed. Histopathological diagnoses included polyps in the vagina, cervix or uterus ( n  = 8), hyperplastic lesions of the endocervix ( n  = 10) and seven adenomas and two adenocarcinomas of the endocervix. Endometrial alterations included single small glandular cysts ( n  = 3), nodular glandular–cystic hyperplasia ( n  = 8), adenoma ( n  = 20) and adenocarcinoma ( n  = 3). Four placentas, 10 focal decidualizations and six deciduomas were found. Furthermore, 18 leiomyomas and nine leiomyosarcomas were diagnosed. Uterine malignant mixed Müllerian tumours were observed in seven cases. Overall, benign lesions outnumbered malignant tumours in the female genital tract of pet guinea pigs. Therefore, surgical excision or ovariohysterectomy should be recommended as therapy.